2014
DOI: 10.1038/srep06803
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry applied to virus identification

Abstract: Virus detection and/or identification traditionally rely on methods based on cell culture, electron microscopy and antigen or nucleic acid detection. These techniques are good, but often expensive and/or time-consuming; furthermore, they not always lead to virus identification at the species and/or type level. In this study, Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) was tested as an innovative tool to identify human polioviruses and to identify specific viral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
96
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 34 publications
(43 reference statements)
1
96
0
1
Order By: Relevance
“…On the contrary, in this study, echovirus type 30 and cytomegalovirus were added having been found them by cultivated clinical samples in a number of respiratory tract infections in our laboratory. MALDI-TOF MS is strictly dependent on the viral concentration in the sample and on the presence of molecules deriving from cell debris24. The present study demonstrated that with a minimum concentration of 10 6 TCID 50 /μl it is able to discriminate between virus infected and uninfected cell cultures.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…On the contrary, in this study, echovirus type 30 and cytomegalovirus were added having been found them by cultivated clinical samples in a number of respiratory tract infections in our laboratory. MALDI-TOF MS is strictly dependent on the viral concentration in the sample and on the presence of molecules deriving from cell debris24. The present study demonstrated that with a minimum concentration of 10 6 TCID 50 /μl it is able to discriminate between virus infected and uninfected cell cultures.…”
Section: Discussionmentioning
confidence: 54%
“…The obtained results are unexpected, especially considering that a discrimination among adenovirus C types and parainfluenza types reference strains has been successful by using a discovery biomarkers software (ClinProTools), as also previously observed for poliovirus types24. This could be also a consequence of the fact that enveloped viruses have the capability of incorporating some host proteins packaged into their envelope29.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Mass spectrometry (MS) and mainly matrixassisted laser desorption ionization-mass spectrometry (MALDI-MS) has grown tremendously as a powerful tool to analyze secondary metabolites of microorganisms 7 and other species such as virus, 8 Imaging mass spectrometry (IMS) that incorporates spatial distribution is an emerging and promising new technology for metabolomics MS analysis. This methodology was introduced in 1997 by Caprioli et al 12 and mostly applied to create 2D images based on the spatial distribution of peptides and protein across the surface of intact biological tissues.…”
Section: Maldi Imaging Mass Spectrometry Of Fresh Water Cyanobacteriamentioning
confidence: 99%